In Silico Studies on The Potential of Green Tea Catechin Compounds (Camellia sinensis) as Antiviral of SARS CoV-2 Againts Spike Glycoprotein (6LZG) and Main Protease (5R7Y) - Futna Naufa; Roihatul Mutiah; Yen Yen Ari Indrawijaya (Journal of Food and Pharmaceutical Sciences, 2022)
COVID-19 is a disease caused by SARS CoV-2 by producing structural proteins and non-structural proteins. SARS CoV-2 uses a spike glycoprotein to bind ACE-2 receptors in host cells and uses main protease to replicate. This research aims to screen green tea catechin derivates as an antiviral for SARS CoV-2 through inhibition of spike glycoprotein (6LZG) and main protease (5R7Y). In silico studies carried out are molecular docking, prediction of physicochemical properties, and prediction of toxicity. The potential inhibition was assessed based on binding affinity and interaction of amino acid residues. From the molecular docking process showed that epicatechin and epigallocatechin provide inhibition to spike glycoprotein better than nafamostat indicated by binding affinity of -5.2 kcal/mol and -4.5 kcal/mol, while epigallocatechin gallate and epicatechin gallate provide inhibiton to main protease better than lopinavir with binding affinity of -8.7 kcal/mol and -8.3 kcal/mol. The results of the physicochemical properties prediction showed that only epigallocatechin gallate that did not fulfill five Lipinski's rule. Based on the toxicity class LD50, the derivates of catechin belong to classes 4 and 6. In conclusion, it can be known that epicatechin and epigallocatechin can be developed as an antiviral for SARS CoV-2.